1984
DOI: 10.1080/00071668408454900
|View full text |Cite
|
Sign up to set email alerts
|

Effect of semen storage time and number of spermatozoa inseminated on the fertility and hatchability of eggs from dwarf broiler breeder hens

Abstract: Semen from commercial breeder males was diluted two-fold and stored for 6 and 24 h at 2 to 3 degrees C. For each storage period, groups of caged dwarf broiler breeder hens from the same strain were inseminated with 300, 200 or 100 x 10(6) spermatozoa. Three replicates of 15 birds were inseminated per treatment. Control hens were inseminated with 150 x 10(6) fresh, undiluted spermatozoa. Inseminations were performed for 5 consecutive weeks during a first (32 to 36 weeks of age) and for 6 consecutive weeks durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 9 publications
2
4
0
Order By: Relevance
“…Fertility and hatchability obtained with both pure fresh and pure semen stored for 24 h were high, with very small differences between treatments (Table 2). These observations are in agreement with previous studies (Van Wambeke 1984; Van Wambeke and Mestdagh 1986).…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Fertility and hatchability obtained with both pure fresh and pure semen stored for 24 h were high, with very small differences between treatments (Table 2). These observations are in agreement with previous studies (Van Wambeke 1984; Van Wambeke and Mestdagh 1986).…”
Section: Resultssupporting
confidence: 94%
“…Using the storage method described here, previous experiments (Van Wambeke 1984) have shown that optimum fertility and hatchability after 24 h of storage were obtained with weekly inseminations, varying from 200 to 300 x lOb sp. hen-r.…”
Section: Birdsmentioning
confidence: 97%
“…In our experiments, the fertilization rates obtained with spermatozoa stored for 24 h at 4°C over the first 8 weeks of the experiment were as high as the highest levels reported in the literature (Lake & Ravie, 1979;Van Wambeke, 1984). In the young animals, there were no significant differences between fresh unstored semen and most of the treatments of semen stored for 24 h. It is possible that the number of fertile spermatozoa was so high that it partly masked the effects of the treat¬ ments on fertilization rates (Wishart, 1985).…”
Section: Discussionsupporting
confidence: 63%
“…The situation is more confusing for stored semen. Lake & Ravie (1979) and Van Wambeke (1967, 1984 reported high fertility (89-97%) for cock semen stored for 24 h at 2-5°C in semen containing homologous seminal plasma and artificial diluents.…”
Section: Effects Of Seminal Plasma On In Vitro Storage Of Spermatozoamentioning
confidence: 99%